Postpartum breast complications and breast-feeding practices in a baby-friendly hospital in Bangladesh - Ara, Rifat; Previn, Shahana; Yeasmin, Dilruba; Haque, Farhana; Akhter, Tohmina; Afroz, Rumana; Akhter, Sayeba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Breastfeeding is essential for health of both infants and mothers, but it often encounters challenges such as postpartum breast complications. These issues can adversely affect maternal health and significantly hinder success of breastfeeding practices. Aim of study was to assess postpartum breast complications and breast-feeding practices. Methods: This cross-sectional study was conducted in department of obstetrics and gynaecology, Dhaka medical college hospital, Dhaka, Bangladesh from February 2006 to July 2006. Two hundred patients in the postnatal ward who delivered their babies at DMCH were randomly selected. Result: Among 200 postnatal women, 33.5% experienced breast problems. Women with breast problems were designated as group A and women without breast problems were designated as group B. Most women in groups A and B were aged between 21-30 years with average 24.8 years for both groups. Antenatal check-ups were similar across groups, with breastfeeding advice given to 55.2% in group A and 64.7% in group B pre-lacteal feeds were given to 19.4% of group A and 21.8% of group B neonates, while colostrum was fed to the majority. Most neonates were breastfed within 2 hours. Good breastfeeding position and attachment were observed in most cases. Exclusive breastfeeding was more common in group B (73.7%) than in group A (58.2%). Breast problems in group A included engorgement, lactation insufficiency, and nipple issues. Conclusions: The study reveals that postpartum breast complications, notably breast engorgement and lactation insufficiency, significantly affects the breastfeeding effectiveness of new mothers.